A ludicidade e a criança: (des)arranjos no ensino fundamental de nove anos - Azevedo, Nair Correia Salgado de [UNESP] (2010)
The anticipation of the beginning of Elementary School for six-year-old children, recently imposed by the Brazilian federal law, brought controversies and debates about the organization of the curriculum, routines, contents and activities, spaces and objects, conduct of behavior of teachers and parents, as well as about the policies of teachers’ training, amongst other issues. The present article, supported by advances of scientific production on children formal education, considers the changes in the concepts of children education and, consequently, in curricular practices. For this purpose, games and fun are taken as object of analysis and discussion, and the playfulness is proposed as a central curricular axle in the initial years of Elementary Education.